Global Posttrauma Symptoms: A Systematic Review of Qualitative Literature. (April 2020) - Michalopoulos, Lynn Murphy; Meinhart, Melissa; Yung, Justina; Barton, Samuel Monroe; Wang, Xinyi; Chakrabarti, Urmi; Ritchey, Megan; Haroz, Emily; Joseph, Nakita; Bass, Judith; Bolton, Paul
Exposure to potentially traumatic events is a global health problem, especially in low- and middle-income countries. Assessments for symptoms resulting from trauma exposure rely heavily on the Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5) criteria for post-traumatic stress disorder (PTSD), which may not be relevant in all regions of the globe. We examined posttrauma symptoms that were not limited to Western constructs of mental health (i.e., PTSD). In a systematic review, we searched nine databases to identify posttrauma symptoms arising in qualitative literature published before July 17, 2017. A total of 17, 938 records were identified and 392 met inclusion criteria. The 392 studies represented data on 400 study populations from 71 different nationalities/ethnicities. The presence and frequency of posttrauma symptoms were examined across all regions. Fisher's exact tests were also conducted to compare frequencies in posttrauma symptoms across region and gender. Based on a weighted analysis across regions, a list of global posttrauma symptoms ( N = 85) was compiled into an item bank. We found that the majority of DSM-5 PTSD symptoms were mentioned across regions (with the exception of inability to recall specific aspects of the trauma and blame of self or others for the event ). Across all regions, we also found a number of symptoms mentioned that were not part of PTSD and its associated features. Findings suggest that assessing posttrauma symptoms solely based on PTSD may be limiting to global populations. Research, policy, and practice implications are discussed.